Sagot :
x2 − 2x > 0
Convert the inequality to an equation.
x2 − 2x = 0
Factor x out of x 2 − 2x.
x ( x − 2 ) = 0
If any individual factor on the left side of the equation is equal to 00, the entire expression will be equal to 00.
x = 0 x = 0
x − 2 = 0
Set x equal to 0.
x = 0
Set x − 2 x - 2 equal to 0 and solve for x.
x = 2 x = 2
The final solution is all the values that make x ( x − 2 ) = 0 true.
x = 0, 2 x = 0,2
Use each root to create test intervals.
x < 0 x < 0
0 < x < 20 < x < 2 l
x > 2
Choose a test value from each interval and plug this value into the original inequality to determine which intervals satisfy the inequality.
x < 0 x < 0 True
0 < x < 20 < x < 2 False
x > 2 x > 2 True
The solution consists of all of the true intervals.
x < 0 x < 0 or x > 2
pa brainliest answer,,